Metabarcoding analysis reveals an interaction among distinct groups of bacteria associated with three different varietals of grapes used for wine production in Brazil - Rezende, G. S. (2024)
Grapes are globally popular with wine production being one of the most well-known uses of grapes worldwide. Brazil has a growing wine industry, and the Serra Gaúcha region is a significant contributor to the country's wine production. Nonetheless, other states are increasing their relevance in this segment. Environmental factors and the soil microbiome (bacteria and fungi) heavily influence grape quality, shaping the crucial “terroir” for wines. Here, soil quality was assessed through nutrient analysis and bacteria microbial diversity, which could significantly impact grape health and final wine attributes. Soil samples from São Paulo's vineyards, focusing on Syrah, Malbec, and Cabernet Sauvignon, underwent chemical and microbial analysis via 16S rRNA metabarcoding and highlighted significant differences in soil composition between vineyards. Statistical analyses including PCA and CAP showcased region-based separation and intricate associations between microbiota, region, and grape variety. Correlation analysis pinpointed microbial genera linked to specific soil nutrients. Random Forest analysis identified abundant bacterial genera per grape variety and the Network analysis revealed varied co-occurrence patterns, with Cabernet Sauvignon exhibiting complex microbial interactions. This study unveils complex relationships between soil microbiota, nutrients, and diverse grape varieties in distinct vineyard regions. Understanding how these specific microorganisms are associated with grapes can improve vineyard management, grape quality, and wine production. It can also potentially optimize soil health, bolster grapevine resilience against pests and diseases, and contribute to the unique character of wines known as terroir.